PEMBINAAN KELOMPOK PEMELIHARA AZOLLA MICROPHYLLA DI DESA SUNGAI KAYU ARA, SIAK - Irwan Effendi; Afrizal Tanjung; Syahril Nedi; Syafruddin Nasution; Elizal Elizal (Universitas Lancang Kuning, 2018)
Sungai Kayu Ara Village, Siak Regency, Riau Province is a coastal village. The main livelihoods of the people in this village are farming, fishermen and breeders. Pellets and concentrate feed have been used by the community as fish and livestock feed. But the high price of this feed makes this business less profitable. Azolla microphylla as fish feed and livestock has been introduced in Indonesia. This community service activity aims to train coastal communities of A. microphylla cultivation techniques which will later be used as fish feed and other livestock. This activity was carried out with the following stages; 1) Location survey, group formation and coordination. 2) Get off to the field and prepare sites for training. 3) Training of growing substrate fermentation techniques A. microphylla. 3) Training to prepare A. microphylla growing containers. 4) Cultivation training of A. microphylla. 5) Harvesting and giving A. microphylla to livestock. 6) Monitoring and evaluating the results of the trainings. A group of cultivators of A. microphylla has been formed and training has also been carried out with the students of the 2018 UNRI LPPM KKN participants in this village. This group named